MENGENAL MAKROALGA Turbinaria DAN PEMANFAATANNYA - Tri Handayani (OSEANA, 2018)
KNOWING MACROALGAE Turbinaria AND THEIR USAGES. Turbinaria is a member of brown macroalgae that can be found in almost all Indonesian waters. Turbinaria is often regarded as Sargassum because they have a similar morphology and both belong to the Family Sargassaceae. There are 35 species of Turbinaria in the world and 11 of which can be found in Indonesia. Turbinaria conoides, T. decurrens and T. ornata are the most common ones in Indonesian waters. Turbinaria grows on rocky intertidal coastlines, tidepools and reef flats. The life cycle of Turbinaria occurs through alternations between sexual and asexual. Their biphasic life cycle contains gametophytes and sprorophytes. In their sexual reproduction, sporophytes resulted from the germination of zygotes formed by fusion (fertilization) of male and female gametes. Asexual spores develop from both sporophytes and gametophytes. Turbinaria was commonly used as a source of alginate, fucoidan and other bioactive polysaccharides (antioxidant, anticancer, antibacterial, anticoagulant, antiploriferative and antivirus activities).